LASER COMBUSTION ANALYSIS OF δ34S OF SULFOSALT MINERALS - DETERMINATION OF THE FRACTIONATION SYSTEMATICS AND SOME CRYSTAL-CHEMICAL CONSIDERATIONS - Wagner T.; Boyce A.J.; Fallick A.E. (My University, 2002)
Laser sulfur combustion in the presence of O2 is the most commonly used method of in situ sulfur isotope analysis. Previous workers indicated that a small but reproducible fractionation of 34S/32S exists between the product SO2 gas and the mineral. The magnitude of this fractionation varies with bond strength, as reflected in Gibbs free energy of formation at 298.15K. The correction factors are known for common sulfides and anhydrite but not, hitherto, for stibnite and the sulfosalt minerals, which are important constituents of many classes of ore deposits. We present the correction factors for the following chemically and crystallographically well-characterized minerals: stibnite (weighted mean = -1.2%%), bournonite (+0.6%%), tetrahedrite (+1.3%%), and boulangerite (+1.4%%). The Gibbs free energies of formation of these phases have been approximated by the sulfide summation method, and the correlation of ΔG2980 with the correction factor for the sulfosalts fits well with the trend previously established for simple sulfides. There is an excellent correlation between the fractionation factor and mineral composition, a parameter that does result in bond strength variations (e.g., mol fraction of PbS in sulfosalts), allowing estimation of the correction factors for simple intermediate compositions. Finally, bond strength also varies with variation in interatomic distances, and we have, therefore, investigated the behaviour of stibnite, a strongly anisotropic mineral. Our results indicate that there is a significant variation in fractionation factor, depending on crystal orientation. The fractionation factor along the prismatic b-axis, which displays the strongest chemical bonds (as monitored by the shortest bond lengths), is more negative (-1.7%%) than along the other crystallographic directions (-0.7 to -1.0%%), which is in full agreement with theoretical predictions. We demonstrate the application of the technique in unravelling source- and process-related sulfur isotope systematics in two hydrothermal vein systems in the classic mining area of the NE Rhenish Massif, both studies requiring resolution beyond the scale of conventional sulfur isotope analysis.